A Novel Brevinin2 HYba5 Peptide against Polymicrobial Biofilm of Staphylococcus aureus and Enterococcus faecalis - Radhakrishnan, Megha P.; Suryaletha, Karthika; Joseph, Iype; George, Sanil; Thomas, Sabu (Protein and Peptide Letters, 2023)
Background: Brevinin2 HYba5 (Peptide 29) is a novel cationic peptide identified from an endemic frog, Hydrophylax bahuvistara. Staphylococcus aureus and Enterococcus faecalis are troublesome biofilm-forming pathogens associated with nosocomial and community-acquired infections and contribute to the severity of infections associated with implanted devices and chronic wounds. Co-existence of both pathogens in biofilm mode contributes to an increased antibiotic resistance, treatment failure and hence persistent disease burden. Identifying a novel and stable, less toxic compound targeting multispecies biofilm with a lower probability of acquiring resistance in comparison to antibiotics is highly warranted.Objective: Evaluate the activity of Brevinin2 HYba5 against S. aureus and E. faecalis mixed biofilm.Methods: The anti-biofilm activity of peptide 29 was tested by Crystal violet assay, Confocal laser scanning Microscopy (CLSM) and MTT Assay. Cytotoxicity of the peptide was tested in RBC and L929 fibroblast cell line. Biofilm inhibitory activity of the peptide was evaluated at different temperatures, pH, serum and plasma concentrations. The antibiofilm potential of the peptide was tested against polymicrobial biofilm by Fluorescent in situ hybridisation (FISH) and plate counting on HiCromeTM UTI Agar media.Results: The peptide 29 could inhibit biofilm formation of S. aureus and E. faecalis individually as well as in polymicrobial biofilm at 75 μM concentration. The peptide maintained its antibiofilm potential at different temperatures, serum and plasma concentrations. Activity of the peptide was high at acidic and neutral pH but found to get reduced towards alkaline pH. The peptide is nonhemolytic and does not exhibit significant cytotoxicity against the L929 fibroblast cell line (92.80% cell viability).Conclusion: The biofilm inhibition property makes peptide 29 a promising candidate for the management of S. aureus and E. faecalis biofilm, especially in catheter-associated devices to prevent the initial colonization and thus can ease the burden of pathogenic biofilm-associated infections.
Keywords: Antibiofilm activity